Introduction of a surgical Black Box system in a hybrid angiosuite: Challenges and opportunities. (August 2020) - Doyen, Bart; Gordon, Lauren; Soenens, Gilles; Bacher, Klaus; Vlerick, Peter; Vermassen, Frank; Grantcharov, Teodor; Van Herzeele, Isabelle
Highlights: The OR Black Box® is a comprehensive data capture platform for quality improvement. This system has been installed in a hybrid angiosuite for the first time worldwide. Captured data facilitates evaluation of (non-)technical skills and radiation safety. Detailed analysis of (near-miss) errors and distractions may augment team feedback. Black box technology may improve team and patient safety in endovascular surgery. Abstract: Purpose: In laparoscopy, the Operating Room Black Box® (ORBB) provides insights into operative performance to improve patient safety. This technology may also enhance endovascular surgical practice; however, the use of a C-arm and X-rays pose important challenges, hindering transferability to an endovascular context. We describe the first implementation of ORBB technology in a hybrid angiosuite and illustrate its value in evaluating surgeons' radiation safety, technical and non-technical performance. Methods: Team members (surgeons, nurses, anaesthesiologists) and stakeholders were informed during several information sessions. Together with teams from Surgical Safety Technologies (Toronto, Canada), an implementation plan was developed, and video-evaluation frameworks were chosen. Radiation safety was assessed using dose measurements and video-evaluation of safety-related behaviours. Technical performance was assessed using 'global' (GRS) and 'procedure-specific' (PRS) rating scales and the 'EndoVascular Aortic Repair Assessment of Technical Expertise' (EVARATE) framework. Surgeons' non-technical skills were assessed with the NOTSS framework. Results: The system captures Audio-visual data from four ceiling-mounted cameras, three ceiling-array microphones, the fluoroscopy screen and anaesthesia monitor. After patient and team consent, an elective endovascular aneurysm repair was successfully analysed. Dose-Area-Product and Air Kerma were 71094 mGy.cm 2 and 270 mGy, respectively. Behavioural analysis revealed deficiencies in stepping back and radiation safety communication. Technical skill assessment was feasible: GRS: 29/40; 'PRS': 27/35; EVARATE: 29/35. Non-technical analysis highlighted surgeons' leadership qualities. Conclusion: An innovative data capture platform has been successfully installed to evaluate overall performance during endovascular procedures. This technology may facilitate identification of (radiation) safety-related errors and instigate educational interventions based on real-world issues.